How Rotating Solar Atmospheric Jets Become Kelvin–Helmholtz Unstable - Zhelyazkov, Ivan; Chandra, Ramesh; Joshi, Reetika (Frontiers in Astronomy and Space Sciences, 2019)
The Kelvin--Helmholtz instability (KHI) is a ubiquitous phenomenon across the Universe. Over the past two decades, several space missions have enabled our understanding of this phenomenon at the Sun's atmosphere. Key results obtained by \emph{Hinode\/} and Atmospheric Imaging Assembly on board the \emph{Solar Dynamics Observatory\/} allowed us to get useful data concerning the physical parameters of various solar jets and the characteristics of detected waves and instabilities in those structures. The rotating solar jets are among the most spectacular events in our Sun. They support the propagation of a number of magnetohydrodynamic (MHD) modes which, under some conditions, can become unstable and the developing instability is of the KH kind. In its nonlinear stage the KHI can trigger the occurrence of wave turbulence which is considered as one of the basic mechanisms of the coronal heating. The modeling of tornado-like phenomena in solar chromosphere and corona as moving weakly twisted and spinning cylindrical flux tubes shows that the KHI rises at the excitation of high-mode MHD waves. The instability occurs within a wavenumber range/window whose width depends on the MHD mode number \emph{m}, the plasma density contrast between the rotating jet and its environment, as well as on the twists of the internal magnetic field and jet's velocity. We have studied KHI instability in a twisted solar polar coronal hole jet, in a twisted rotating jet emerging from a filament eruption, and in a rotating macrospicule. It has been established that good agreement between the theoretically calculated KHI developing times of a few minutes at wavelengths comparable to the half-widths of the jets, and those growth times detected from observations can be achieved at the excitation of high (9 $\mathrm{\leqslant}$ \emph{m} $\mathrm{\leqslant}$ 52) MHD modes only.